2020
DOI: 10.2147/ijgm.s252651
|View full text |Cite
|
Sign up to set email alerts
|

<p>Early DNR Order and Long-Term Prognosis Among Patients Hospitalized for Acute Heart Failure: Single-Center Cohort Study in Japan</p>

Abstract: An early do-not-resuscitate (DNR) order is classified as such when it occurs within 24 hours of admission. Early DNR has been previously associated with in-hospital mortality among acute heart failure (AHF) patients and one-year mortality among patients discharged from ICU. Here, we investigate whether early DNR is associated with long-term mortality in AHF Japanese patients, by performing a retrospective cohort study. Patients and Methods: We retrospectively investigated all patients with AHF, admitted to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…We found no differences between sexes in adjusted 1-year mortality after ICH. However, DNR orders may worsen outcomes independently in ICH patients ( 29 32 ) and it is possible that the increased use of DNR orders in women in our study may have contributed to a decreased survival.…”
Section: Discussionmentioning
confidence: 82%
“…We found no differences between sexes in adjusted 1-year mortality after ICH. However, DNR orders may worsen outcomes independently in ICH patients ( 29 32 ) and it is possible that the increased use of DNR orders in women in our study may have contributed to a decreased survival.…”
Section: Discussionmentioning
confidence: 82%
“…Usually, patients decide to sign DNAR forms before high-risk operations such as neurosurgical operations which may lead to a coma or a vegetative state. Other reasons for deciding to sign it is when a person is in the terminal stage of a chronic illness which is uncurable, so the performance of CPR, if needed, will only prolong the suffering of the patient for some time [ 6 , 7 ]. The use of the DNAR protocol is more prevalent among emergency patients and is associated with age and non-trauma presentation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the mortality rate was higher in patients who signed a DNR order in the intensive care unit (ICU) [ 4 , 8 ]. Studies have also shown that a DNR order was associated with high mortality in patients with heart failure and sepsis [ 9 , 10 , 11 ]. Hence, whether a DNR should be determined very early, while patients are still in the emergency department (ED), remains controversial.…”
Section: Introductionmentioning
confidence: 99%